Non Traumatic Hip Osteonecrosis Treated By Non Vascularised Bone Graft Versus Core Decompression - Hassan, Dhary F.; Majeed, Ghadeer H.; Al-Sudani, Abed Falih (AL-Kindy College Medical Journal, 2016)
Background: Avascular necrosis (AVN) is defined as cellular death of bone components due to interruption of the blood supply; the bone structures then collapse, resulting in bone destruction, pain, and loss of joint function. AVN is associated with numerous conditions and usually involves the epiphysis of long bones, such as the femoral head. In clinical practice, AVN is most commonly encountered in the hip. Early diagnosis and appropriate intervention can delay the need for joint replacement. However, most patients present late in the disease course. Without treatment, the process is almost always progressive, leading to joint destruction within 5 years.Treatment of a vascular necrosis depends mainly on early diagnosis which mainly based on clinical findings, x-ray finding & MRI.A variety of non vascularized bone grafting techniques have been proposed with varying degrees of success as treatment alternatives for osteonecrosis of the femoral head. The success of these procedures may be enhanced using ancillary growth and differentiation factors. Objectives: To treat non traumatic hip osteonecrosis by non vascularized bone graft versus core decompression. Type of the study: A retrospective study. Methods: We retrospectively reviewed 72 patients (88 hips) with osteonecrosis of the femoral head between May 2009, and March 2014,divided into two groups . Group A include 34 patients (44 hips) with osteonecrosis of the femoral head who had non vascularized bone grafting procedures done for them . Minimum follow-up was 12 months. We compared the outcomes in this cohort to similar hip number (44 hips) in 40 patients treated with core decompression only (group B). We used Phemister technique to make a window at the posterior aspect of greater trochanter to remove necrotic bone and packed the excavated area with autogenous cancellous bone graft taken from ipsilateral iliac crest or leave it without bone graft (decompression only). Results: We report the result of treatment for femoral head avascular necrosis depending on Ficat classification stage I, II, & III. The minimum follow up was 12 months (12m-36m). The success percentage of hips in our cohort of patients with non vascularized bone grafting group A are 86% (38 of 44 hips), which is higher than group B 63% (28 of 44 hips) with core decompression alone. Conclusions: These procedures core decompression and autogenous cancellous bone graft may defer joint arthroplasty in selected patients & it is more effective than core decompression alone in treating early stages of femoral head osteonecrosis.